Application Of Cooperative Integrated Reading And Composition Learning Model To Improve Reading Comprehension Skills In Indonesian Language Subjects For Class IV Students UPT SPF SDN Garuda Kota Makassar - Rahman, Nurhijriani; Atjo, Syamsuryani Eka Putri; Amin, Muhammad (International Journal of Elementary School Teacher, 2025)
This study aims to improve the reading comprehension skills of fourth grade students of UPT SPF SDN Garuda Makassar City in Indonesian language subjects using the cooperative integrated reading and composition learning model. The approach used in this research is a qualitative approach, with the type of classroom action research. The subjects used in this study were class IV UPT SPF SDN Garuda students totaling 24 students. Data collection techniques were observation, tests, and documentation. The data from this study were analyzed qualitatively and quantitatively. The results showed that there was an increase in teacher teaching activities, student learning activities, and students' reading comprehension skills. The results of teacher teaching observations in cycle I were in the good category and in cycle II were in the good category. The results of student observations in cycle I were in the moderate category while in cycle II there was an increase to the good category. The results of the reading comprehension ability test also increased, as evidenced in cycle I was in the incomplete category while cycle II increased to the complete category. So, it can be concluded that the application of the cooperative integrated reading and composition learning model can improve reading comprehension skills in Indonesian language subjects for class IV UPT SPF SDN Garuda Makassar City.